State of Art of Cooling Method for Dry Machining - Kaaliarasan, Ramachandran; Balakumaran, Yeesvaran; K., Kadirgama; D., Ramasamy; S. A., Che Ghani; Keeran, Anamalai (EDP Sciences, 2016)
The usage of cutting fluid in the machining operations will not only poses a health risk to the workers but also creates environmental challenges associated with fluid treatment and disposal. In an effort to minimize these concerns, various cooling method have been reviewed and the comparison among them have been tabulated. Internal cooling system for dry machining has a promising future in adaptive machining to produce contamination free products. This paper also highlights the novel feature for cooling system to improve dry machining which uses the conventional turning machine. This developed novel feature is ecologically desirable and it will be considered as a necessity for dry machining in the near future.